Sintesis Senyawa Bioaromat Melalui Proses Siklisasi Katalitik Gugus Asam Lemak α-eleostearat Dalam Minyak Kemiri Sunan - Vincensia Michelle; Tedi Hudaya; Tatang Hernas Soerawidjaja (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Kemiri sunan oil (Reutalis trisperma) is a non-edible vegetable oils which thrives in Indonesia, has α-eleostearic acid that can be processed into aromatic compound through isomerization-cyclizationdisproportionation.The purpose of this research was knowing kemiri sunan oil’s potency for synthesizingaromatic compound and the effects of the reaction’s condition and solvent : feed ratio to the yield of cycliccompound. This research was initiated by testing kemiri sunan oil quality by several tests: acid number,iodine number, and saponification number. Saponification was done using KOH at 60°C ; 3 hours. Then,Mg(NO3)2 was added as substituent for K in base soap and Cr(NO3)3 as a catalyst. Obtained Mg soap wasthen cleaned using aquadest before dried in the oven until its mass was constant at 60°C, then diluted inDiethanolamine. The reaction was held for 2 hours with the variations of temperature and ratio of solvent :feed (w/w). The product was then extracted using toluene in order to gain all of the aromatic compound.Then, the separation of the solvent from the product was done using simple distillation. Cyclic productpresence in the form of ortho-disubstituted benzene was tested qualitatively using FTIR, while thequantitative tests were conducted by Wijs test and aromatic product’s mass calculation.